USE OF NEW TYPES OF SLIDE SHUTTERS IN THE JSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - I. A. Bondarenko; A. K. Turygin; A. L. Artamoshin; A. V. Vengura (Литьë и металлургия, 2016)
Testing the slide shutters of a new design of «book» type and refractory materials for shatters from a number of suppliers are carried out.